Petermann 2015 Expedition - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during July to September 2015 - Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2017)
Petermann 2015 was an international research expedition to the area around the Petermann glacier in northwestern Greenland. The Swedish icebreaker Oden served as the platform for the research carried out in the sea, on the glacier and on land.

The expedition examined the relatively unexplored outlet end of this large system, by documenting changes in the grounded Petermann Glacier, its buttressing ice shelf, and ocean conditions since the end of the last glacial period. Primary scientific questions included:
How sensitive is Petermann ice shelf extent to documented climate changes within the Holocene?
Is ice-shelf response independent of, or linked to, variations in the grounded Petermann Glacier, ocean thermal conditions, or relative sea level (i.e., sill depth)?
What are the rates of change and variability of these systems in response to early Holocene warming, Neoglacial cooling, and post-Neoglacial (late 19th century to present) warming?

Purpose:

The purpose of the project was to collect multibeam bathymetry and sub-bottom profile information along the western continental shelf of Greenland in order to characterize the shape of the seafloor and uppermost sediment properties. The main goal was to increase our understanding about potential pathways of relative warmer water influx towards Greenland’s many outlet glaciers.

This data set contains meteorological, oceanographic and ship data collected during the International expedition Petermann, which was an international research cruise using the icebreaker Oden in the Arctic Ocean.

Data include meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure, Cloud height/cloudiness, Photosynthetic Active Radiation (PAR).

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.

Petermann 2015 var en svensk-amerikansk forskningsexpedition som gick till området kring Petermannglaciären på nordvästra Grönland. Den svenska isbrytaren Oden fungerade som plattform för den forskning som utfördes i havet, på glaciären och på land.

Expeditionen undersökte det relativt outforskade utloppet av den stora glaciären genom att dokumentera förändringar hos fastlandsdelen av Petermannglaciären, dess flytande shelfis och havsförhållandena sedan slutet av den senaste istiden.
Expeditionens övergripande frågeställningar är hur shelfisens utbredning påverkats av de naturliga klimatförändringarna sedan vår senaste istid och om isens förändringar är oberoende av, eller kopplade till, förändringar i den landfasta Petermannglaciären, havsvattentemperatur och den relativa havsnivån. Huvudfokus är även frågan om vilken betydelse klimatförändringarna haft för utbredningen av shelfisen under den tidiga istiden, den lilla istiden och perioden sedan 1800-talets slut. Genom återkommande mätningar, såväl i fjordarna som i is och sediment på land vill forskarna bättre förstå dynamiken som ligger bakom smältningen av glaciären, vad som är naturligt återkommande och vad som är mänsklig påverkan.

Syfte:

Syftet med projektet var att samla in data utmed Grönlands västra kontinentalsockel för att bedöma strukturen på havsbotten och egenskaperna för de översta sedimenten. Huvudmålet var att öka förståelsen om potentiella vägar för relativt sett varmare vattenflöden mot Grönlands många utloppsglaciärer.

This data set contains meteorological, oceanographic and ship data collected during the International expedition Petermann, which was an international research cruise using the icebreaker Oden in the Arctic Ocean.

Data include meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure, Cloud height/cloudiness, Photosynthetic Active Radiation (PAR).

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.
Petermann-expeditionen 2015 - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden under juli till september 2015
Keywords: Meteorology; Meteorologi; ATMOSPHERE; ATMOSPHERIC WINDS; SURFACE WINDS; ATMOSPHERIC TEMPERATURE; AIR TEMPERATURE; ATMOSPHERIC WATER VAPOR; HUMIDITY; CLOUDS; ATMOSPHERIC PRESSURE; SURFACE PRESSURE; SALINITY; CONDUCTIVITY; PHOTOSYNTHETICALLY ACTIVE RADIATION; WATER TEMPERATURE; WATER DEPTH; SEAFLOOR TOPOGRAPHY; BATHYMETRY; BIOSPHERE; VEGETATION; The icebreaker Oden; Isbrytaren Oden; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Engineering and Technology; Teknik; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav; Environment; Miljö